2006
DOI: 10.1109/tps.2006.879179
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of BCN Films Deposited at Various$hboxN_2/hboxAr$Flow Ratios by DC Reactive Magnetron Sputtering

Abstract: In this paper, boron carbonitride films were deposited by a dc reactive unbalanced magnetron sputtering of conductive B 4 C target in a mixture gas of nitrogen and argon. The films with various content of N were obtained by a varying N 2 /Ar flow ratio in the mixed gas from 0/100 to 30/100. Structures and compositions of the films were investigated by X-ray photoelectron spectroscopy (XPS) and Fourier transform infrared spectroscopy (FTIR). The results show that the content of B, C, N, and the ratio of each el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…18 The peaks centered at 187.6 and 192.1 eV in Fig. 16,21,23 Both the B1s and the N1s spectra signify that the sp 2 B-N bonding (as in h-BN) is the main configuration for B and N atoms in the present nanosheets. 16,19-21 C has a lower electronegativity than N, therefore due to the lower charge displacement from B to C compared to that from B to N, the B-C subspectrum is observed at a lower binding energy than the B-N subspectrum.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…18 The peaks centered at 187.6 and 192.1 eV in Fig. 16,21,23 Both the B1s and the N1s spectra signify that the sp 2 B-N bonding (as in h-BN) is the main configuration for B and N atoms in the present nanosheets. 16,19-21 C has a lower electronegativity than N, therefore due to the lower charge displacement from B to C compared to that from B to N, the B-C subspectrum is observed at a lower binding energy than the B-N subspectrum.…”
Section: Resultsmentioning
confidence: 81%
“…3b. 15,16,19,[26][27][28] The blue shift of the out-of-plane bending mode to $809 cm À1 (usually reported at 780 cm À1 ) in the present nanosheets can be due to the increase in the bond stiffness, induced by the incorporation of non-BN bonds in the hexagonal network. The broad strong absorption peak at $1380 cm À1 and the peak at $809 cm À1 can be attributed to the in-plane stretching and out-ofplane bending vibration of B-C-N rings, respectively.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…They concluded that the hierarchy of energetic stability of bonds in BCN follows the sequence B–N > C–C > C–N > C–B > B–B > N–N. The same conclusion was reached despite the different depositions method used in these studies, namely plasma CVD [ 20 , 29 ], ion-beam-assisted deposition [ 22 , 30 ], magnetron sputtering [ 31 ], pulse laser deposition [ 32 ], or laser abration [ 33 ].…”
Section: Resultsmentioning
confidence: 77%
“…Various techniques, such as chemical vapor deposition (CVD), 5,6 pulsed laser deposition (PLD), 7,8 ion beam deposition 9 and sputtering 10 have been used to prepare BCN thin films. The BCN films of diverse compositions have been prepared by magnetron sputtering, mainly from co-targets or mixed target (h-BN and graphite).…”
mentioning
confidence: 99%